Angler phishing attacks on social media users in South Africa - Mogashoa, Kemisetso (University of the Witwatersrand, Johannesburg, 2024)
Since its founding, the term ‘phishing’ has expanded significantly as new dynamics and paradigms keep shifting the technology space. New technology platforms have increased individuals’ use of the internet and changed the way in which we communicate forever. Social media has steadily taken over traditional communication mediums, and the adoption is not slowing down anytime soon. What would have previously been sent as an email has now become a five-second WhatsApp message or Facebook post, and businesses are not lagging in this trend. Unfortunately, this has also led to a plethora of increased cybercrimes and has left the ecosphere of cybersecurity perturbed, as organisations scramble to find suitable solutions to combat phishing attacks internally and externally. Seminal works have covered the impact of phishing attacks on organisations and have provided practical solutions as intervention strategies. However, the same cannot be said about individuals and consumers. As businesses start to transform digitally, social media has become an imperative mediator between businesses and consumers, and phishers have taken notice. This has birthed a new form of phishing called angler phishing. This research focused predominately on the experiences of social media users who have been victims of this type of phishing. The study followed an interpretivist paradigm to understand victims’ realities and lived individual experiences. The snowball sampling method was executed to acquire participants, and social media was used to recruit 11 participants. Furthermore, an additional 7 participants consisting of a team of technical experts were interviewed in a focus group to evaluate the conceptual framework. The study incorporated theoretical frameworks such as the Big Five Personality Traits model and the Heuristic-systematic model (HSM) to understand personality types’ role in user behaviour and how users process information can lead to phishing susceptibility. Key findings revealed that whilst angler phishing is a growing trend, South Africa and organisations continue to neglect documenting the severity of these crimes which subsequently contributes to increased cybercriminal attacks. Additionally, the findings revealed cybercriminals continue to evolve and adapt their strategies and techniques alongside the evolution of new technologies. As a result, findings revealed a gap in digital literacy and other factors, such as the environment and cybersecurity training, play a pivotal role in a phishing lifecycle. Furthermore, having reviewed the key theoretical frameworks and the findings from the study, an adapted conceptual framework was presented to include these additional constructs such as the environment and training. v Moreover, recommendations have been presented for both social media users and organisations on what effective interventions can be followed to prevent future attacks. Lastly, the study concludes by providing an all-encompassing view of the background of angler phishing, seminal works from the literature, a research methodology, presentation of key findings and recommendations. Ultimately, organisations and other institutions have a responsibility to ensure consumers are cyber-educated and protected. Noting the limitations of the study, suggestions for future research were provided
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Angler Phishing; Phishing; Social engineering; Cybersecurity; Social media; UCD; SDG-8: Decent work and economic growth